2018
DOI: 10.11606/issn.2176-9419.v20iespecialp95-118
|View full text |Cite
|
Sign up to set email alerts
|

Observações sobre fraseamento prosódico e densidade tonal no Português de Moçambique

Abstract: Este artigo traz uma investigação preliminar do fraseamento prosódico de frases declarativas neutras e sua densidade tonal, no português falado em Moçambique, África, no estilo de fala espontânea. Interessa, portanto, descrever as marcas melódicas das fronteiras de sintagma entoacional: os tipos de acentos tonais e de tons de fronteira, e a ocorrência de pausas silenciosas. A pesquisa faz uso do aporte teórico-metodológico da Fonologia Prosódica e da Fonologia Entoacional Autossegmental e Métrica; a análise ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…That finding, taken together with the possibility of an additional tone on pre-stressed syllables in long words, led to the conclusion that the neutral declaratives produced by the Mozambican speaker in reading style displayed high tonal density, in line with the tendency of the other African varieties. In spontaneous MP speech, however, 43.2% of tonal accents were associated with internal PWs (Serra & Oliveira, 2018), a considerably lower number than found in the sentence reading task in this study. It may be thought that the speakers behave differently, but also that the reading task offered clearer contexts for observing tonal density, because it involved controlled phrases which did not offer context for, for example, stress clashes between words.…”
Section: D) Tonal Densitycontrasting
confidence: 86%
See 4 more Smart Citations
“…That finding, taken together with the possibility of an additional tone on pre-stressed syllables in long words, led to the conclusion that the neutral declaratives produced by the Mozambican speaker in reading style displayed high tonal density, in line with the tendency of the other African varieties. In spontaneous MP speech, however, 43.2% of tonal accents were associated with internal PWs (Serra & Oliveira, 2018), a considerably lower number than found in the sentence reading task in this study. It may be thought that the speakers behave differently, but also that the reading task offered clearer contexts for observing tonal density, because it involved controlled phrases which did not offer context for, for example, stress clashes between words.…”
Section: D) Tonal Densitycontrasting
confidence: 86%
“…10 However, either there was insufficient segmental material for the initial rising pitch to be expressed or it was phonetically too discreet. In a previous study, Serra and Oliveira (2018) observed that the falling final contour predominated in the declaratives, with the configuration most produced being H+L* L% (60%). Re-examination of these tokens of spontaneous speech revealed that many cases of H+L* L% could be re-interpreted as LH+L* L%, although the initial rising movement preceding the fall was not all that substantial.…”
Section: C) Nuclear Pitch Accent and Boundary Tonementioning
confidence: 82%
See 3 more Smart Citations